Carer perspectives on overweight, obesity and dental caries in early childhood: findings from a systematic qualitative review - Cheng, Heilok; Chen, Rebecca; Christian, Bradley; Appleton, Jessica; Arora, Amit; Denney-Wilson, Elizabeth (Frontiers in Oral Health, 2025)
IntroductionFormula and bottle feeding behaviours can increase obesity and tooth decay (early childhood caries, ECC) in early childhood, through non-responsive feeding and prolonged exposure to sugar. Parents’ beliefs can be barriers to behaviour change for obesity and ECC prevention. Understanding these beliefs towards children's teeth and weight can address parents’ priorities and develop prevention messages. This qualitative systematic review (PROSPERO registration #CRD42022348783) aimed to identify parent or carer perspectives on obesity and ECC in children aged ≤6 years.MethodsDatabase searching of CINAHL, Medline and EMBASE, with hand searching, was undertaken. Included papers were qualitative research publications, focused on parent or carer beliefs and attitudes towards overweight, obesity or ECC in infants and children. Inductive thematic analysis was undertaken to generate themes, with a strengths-based approach focused on parents’ lived experience. Quality appraisal was undertaken with the CASP Qualitative Checklist. Descriptive characteristics of the study and participants, and qualitative findings, were extracted qualitatively in NVivo.Results7,365 references were identified from database and hand searching, with 98 references included for analysis. Three research themes were generated: (1) parenting to support child wellness, including healthy teeth and weight; (2) parents’ response to unwellness, including identifying symptoms, causes and protective factors for unhealthy weight and teeth; (3) information and resources needed to support healthy weight and teeth. There was high or potential risk of bias in qualitative methodology when studies did not address researcher-participant relationships or rigorous data analysis processes.DiscussionFindings highlight the need for strength-based messages for children's teeth and weight, increased understanding of formula and bottle feeding as obesity and ECC risk factors, and holistic approaches to care by dental and primary care professionals.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42022348783, PROSPERO CRD42022348783.